2021
DOI: 10.1177/1362361321998560
|View full text |Cite
|
Sign up to set email alerts
|

Parenting stress in autism spectrum disorder may account for discrepancies in parent and clinician ratings of child functioning

Abstract: Elevated parenting stress among parents of children with autism spectrum disorder is well-documented; however, there is limited information about variability in parenting stress and relationships with parent ratings of child functioning. The aim of this study was to explore profiles of parenting stress among 100 parents of young children with autism spectrum disorder enrolled in two clinical trials and potential relationships between parenting stress and parent ratings of child functioning at the baseline time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 78 publications
1
12
0
2
Order By: Relevance
“…For example, previous research has shown that parental stress is higher in families where a child has a diagnosis of ASD [43]. This increased parental stress has been shown to affect how parents assess some aspect of their child development in child studies [44]. Although the previously mentioned study did not find stress to affect ratings of expressive and receptive vocabulary, it should be noted that this study assessed parents of older children.…”
Section: Does Age Moderate the Effect Size Or The Mean Difference Of The Expressive And Receptive Vocabulary Size Of The Infant Groups?mentioning
confidence: 61%
“…For example, previous research has shown that parental stress is higher in families where a child has a diagnosis of ASD [43]. This increased parental stress has been shown to affect how parents assess some aspect of their child development in child studies [44]. Although the previously mentioned study did not find stress to affect ratings of expressive and receptive vocabulary, it should be noted that this study assessed parents of older children.…”
Section: Does Age Moderate the Effect Size Or The Mean Difference Of The Expressive And Receptive Vocabulary Size Of The Infant Groups?mentioning
confidence: 61%
“…Another main limitation to the study is the reliance on participant-reported measures in a cross-sectional design. While caregivers are highly sensitive to changes in their child's functioning, with their reported concerns meeting standards for developmental screening test specificity and sensitivity [67], we cannot rule out the possibility that the heightened stress levels during the COVID-19 pandemic can impact caregiver ratings of child functioning, as demonstrated in a previous study [68]. As such, the findings would be stronger if functioning was assessed from multiple sources.…”
Section: Limitationsmentioning
confidence: 78%
“…Third, the relationship between parental distress and parent-reported child EBPs may be due to shared method variance (Podsakoff et al, 2003 ). There is some evidence to show that levels of parenting stress are associated with parental reports of certain domains of child functioning, such as behavioral problems, but not linked with clinician ratings of child functioning (Schwartzman et al, 2021 ). Exploration of relationships between parenting stress and reports of EBPs in other settings (such as teacher-reported EBPs and observational measures of child behavior) is limited.…”
Section: Introductionmentioning
confidence: 99%